2017
DOI: 10.1158/1055-9965.epi-16-0693
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Penetrance of Major Genes and Polygenes for Colorectal Cancer

Abstract: Background While high-risk mutations in identified major susceptibility genes (DNA mismatch repair genes and MUTYH) account for some familial aggregation of colorectal cancer, their population prevalence and the causes of the remaining familial aggregation are not known. Methods We studied the families of 5,744 colorectal cancer cases (probands) recruited from population cancer registries in the USA, Canada and Australia and screened probands for mutations in mismatch repair genes and MUTYH. We conducted mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
283
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(301 citation statements)
references
References 55 publications
(61 reference statements)
10
283
0
8
Order By: Relevance
“…A recent study of a large number of DNA samples from colorectal cancer patients found that one in 45 individuals are MUTYH mutation carriers [136]; these estimates were similar to those from previous studies [137]. Notably, only 12 well-characterized MUTYH variants (such as Y165C, G382D, and several truncating mutations) were tested for, and this prompts concern that such studies may underestimate the prevalence of MUTYH mutations.…”
Section: Mutyh-associated Polyposissupporting
confidence: 54%
“…A recent study of a large number of DNA samples from colorectal cancer patients found that one in 45 individuals are MUTYH mutation carriers [136]; these estimates were similar to those from previous studies [137]. Notably, only 12 well-characterized MUTYH variants (such as Y165C, G382D, and several truncating mutations) were tested for, and this prompts concern that such studies may underestimate the prevalence of MUTYH mutations.…”
Section: Mutyh-associated Polyposissupporting
confidence: 54%
“…Taking, in contrast to previous lower estimations, all four genes into account, the most recent empiric estimation, based on a large North American/Australian registry, calculated carrier frequencies of 1 in 1946 for MLH1 , 1 in 2841 for MSH2 , 1 in 758 for MSH6 and 1 in 714 for PMS2 mutations 36. Based on these frequencies, CMMRD incidence was calculated to be about 1:1 000 000 children of unrelated parents (figure 1).…”
Section: Estimated Frequency Of Cmmrd As a Differential Diagnosis Of Nf1mentioning
confidence: 97%
“…According to Win et al ,36 in the general population one in 279 children tested will be heterozygous for an MMR gene mutation. Particularly in the case of a clearly pathogenic MLH1 or MSH2 mutation, this results is the unintentional diagnosis of Lynch syndrome in a minor.…”
Section: Potential Benefits and Harm Of Cmmrd Counselling And Testingmentioning
confidence: 99%
See 2 more Smart Citations